Keterlibatan dari Brand Loyalty terhadap Brand Satisfaction pada pengguna Smartphone Android - Rusniawaty, Dini; Masnita, Yolanda (Universitas Of Surakarta, 2023)
This study aims to test brand loyalty, brand love, brand attachment, and brand satisfaction as moderation. The sampling technique used was purposive sampling, namely active Android smartphone users with a total of 125 respondents. The data used was by distributing Google Forms. Hypothesis testing using the SEM method. The test results prove that brand satisfaction has a positive effect on brand loyalty, brand love and brand attachment. At the same time knowing the existence of moderation between brand satisfaction on brand loyalty, band love, and brand attachment.